Teaching and Learning in Rural Contexts - Boix-Tomàs, Roser (2015)
On the basis of a review of the literature on rural and mountain education, this article focuses on the importance of the rural territory to the specificity of learning and teaching in rural schools globally. The analysis revealed that rural education has specificities that differentiate it from urban education and that, besides its limitations, offer potential advantages for the processes of teaching and learning for primary education. Moreover, analysis of rural education revealed that it faces threats to its identity, despite its potential benefits for students and the rest of local communities - a fact that justifies the need to strengthen rural education in those contexts and the possibility that general education may learn from it.